PENGARUH KUALITAS PRODUK, STORE ATMOSPHERE, DAN DISCOUNT TERHADAP KEPUTUSAN PEMBELIAN DISTRO HOUSE OF SMITH SEMARANG (Studi Kasus Pada Konsumen Distro House of Smith Semarang) - Hanafitrah, Akbar; widiartanto, widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Nowadays,the development of fashion trends are always updated, many of the production companies engaged in the field of fashion always arise the initiative to always follow the latest trends for products sold in the market. Quality products and follow the latest trends can attract consumer appeal to buy. Considering the increasing competition of retail business, every retail business needs to increase the strength that exist within the company by raising the difference or uniqueness of the company compared with the competitors to be able to attract consumer buying. The purpose of this study is to determine the effect of product quality, store atmosphere, and discounts on the purchase decision of case studies at consumers of the House of Smith area Semarang. This research type is explanatory research. Sampling technique using Incidental sampling method. The number of samples taken as many as 100 respondents. Data were analyzed through validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, t test and F test with SPSS program aid. Based on the results of descriptive analysis, showing the results of research purchasing decisions are in good category of 4.02 percent. Product quality variable is in good category, equal to 3,79 percent. Store atmosphere variables are in good category, amounting to 3.83 percent, variable discount is in the high category, amounting to 3.52 percent. Suggestion in this research is company need to improve product quality especially about characteristic of product assessed by consumer not yet owned by House of Smith. In addition, companies should be more varied in designing its products to attract consumers and consumer purchasing decisions will increase.